Carboxylic acid-functionalized TiO2 nanoparticle-loaded PMMA/PEEK copolymer matrix as a dental resin for 3D complete denture manufacturing by stereolitographic technique. Issue 1 (1st January 2018) - Chen, Shenggui; Yang, Junzhong; Li, Kaiwu; Lu, Bingheng; Ren, Li
ABSTRACT: The main goal of the present investigation was to the synthesis of bioactive TiO2 nanoparticle-incorporated poly(methylmethacrylate)/polyetheretherketone nanocomposite for enhanced antibacterial and biocompatibility characteristics with suitable properties for manufacturing 3D printed stereolitographic dental prosthesis. The carboxylic acid-functionalized TiO2 nanoparticles have been dispersed into the copolymer matrixes through emulsion polymerization method, and the structural and morphological properties were investigated by using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy, and energy dispersive X-ray (EDX) analytical techniques. The FTIR spectrum of synthesized nanocomposites that shows high intense peaks at 2, 970–2, 850 cm −1 is related to the symmetric and asymmetric stretching C-H vibration of methyl and methylene groups of the polymer matrix. The microscopic results of nanocomposite exhibited that functionalized nanoparticles were effectively and uniformly dispersed into the polymer matrix in the absence of particle agglomerations, and it has been given excellent killing efficiency of 99% under dark conditions against bacterial pathogens Escherichia coli and Staphylococcus aureus and also exhibited favorable cell compatibility with dental pulp cells. This facile synthesized nanocomposite was efficaciously employed for denture manufacturing with stereolitographic technique.